OPTIMALISASI PENYELESAIAN KREDIT BERMASALAH DI BANK JATENG CABANG KOORDINATOR SURAKARTA MELALUI KERJASAMA DENGAN KEJAKSAAN NEGERI SURAKARTA - MULYANTO, MULYANTO (Dinamika Hukum, 2018)
Objectives general general of this research is to describe analytically the resolution of non-performing loans in collaboration with the Surakarta District Attorney's Office, while specifically the purpose is to: (1) Know the process of resolving non-performing loans at the Bank Jateng Coordinating Branch Surakarta. (2) Assessing what factors cause the resolution of non-performing loans through cooperation with the Surakarta District Attorney's institution can be more profitable than without cooperation with the Surakarta District Attorney's institution. (3) Understanding the obstacles faced in the settlement of non-performing loans at the Bank Jateng Coordinating Branch Surakarta. This research is a normative juridical study, the type of research is studying document studies, and is descriptive in nature. The study was conducted at Bank Jateng Surakarta Coordinating Branch. The data used is primary, secondary and tertiary legal materials. Data analysis was carried out by reviewing the credit agreement in the practice of granting credit at Bank Jateng Coordinating Branch Surakarta. Results of the study: (1) The process of solving non-performing loans at the Central Java Bank of Surakarta Coordinator is done by non-litigation and litigation. Non litigation method is carried out through deliberation by rescheduling, reconditioning, and restructuring. The method of non-litigation starting from the billing phase also involved assistance / cooperation with the Surakarta District Attorney as State Attorney in the State Civil and Administrative Affairs to resolve the non-performing loans in accordance with the credit agreement made by Bank Jateng Surakarta Coordinator Branch with debtor customers. (2) Factors that cause cooperation with the Surakarta District Attorney are more profitable because the State Prosecutor's Office is a law enforcement agency, and the Prosecutor's Office can powerfully act inside and outside the Court for and on behalf of the State or Government. Some obstacles in the settlement of non-performing loans at the Bank Jateng Coordinating Branch Surakarta are: The existence of debtors with ill intentions, debtors experiencing economic / business problems, limited debtors in understanding and implementing Bank policies. Keywords: Credit agreement, Non-performing loans, Bank Jateng Coordinating Branch Surakarta.